An automated fabrication strategy to create patterned tubular architectures at cell and tissue scales. (14th April 2015) - Othman, Rebeen; E Morris, Gavin; Shah, Disheet A; Hall, Stephen; Hall, Graham; Wells, Keith; Shakesheff, Kevin M; Dixon, James E
Abstract: The use of materials to impose tissue-like architecture at cell resolution will be important if engineered functional replacements for damaged cardiovascular, pulmonary, renal or digestive tissues are to be authentically engineered. Here, we demonstrate a coordinated system for the fabrication and subsequent culture of tubular tissues composed of multiple layers, cell-types and materials with physiological dimensions and defined architectures at cell resolution. We developed an automated tube fabricator that rolls 2D-matrices into 3D-tubular constructs directly from cells, hydrogels and scaffold biomaterials. Coordinated use of surface modification strategies allows 2D cell sheets and cell/biomaterial composites (i.e. hydrogels or electrospun scaffolds) to be fabricated which may be transferred into a perfusion bioreactor in a rapid and standardized procedure. To exemplify our strategy we fabricated structures resembling human mammary artery and gut; these can be imaged in situ and real-time electrical resistance measurements performed of the vessel walls, allowing non-invasive assessment of viability and functionality. Our system allows patterning at cellular resolution with variable tissue thickness, length, luminal diameter, and constituent biomaterial. This inherent flexibility will allow the recapitulation of the complex hierarchical biological architectures and generate functionality found natively in vivo .